Pengaruh Lifestyle dan Financial Planning Terhadap Spending Behavior pada ASN di Kecamatan Pulau Banyak - Hera Nofita Sari; Tio Devilishanti; Fitria Mandaraira; Muzakir Muzakir (Indo Publishing, 2026)
This study is motivated by the importance of understanding the spending behavior of State Civil Servants (ASN), given that a relatively stable income is not always accompanied by sound financial management. Furthermore, there is a lack of research examining this phenomenon among ASN in island regions, specifically in Pulau Banyak District, Aceh Singkil Regency. This study aims to determine how lifestyle and financial planning influence the spending patterns of civil servants in Pulau Banyak District, Aceh Singkil Regency. A quantitative method was employed, involving 64 respondents selected through simple random sampling. Data were collected via questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 25 software. The results indicate that lifestyle does not have a significant effect on spending patterns; however, sound financial planning exerts a positive and significant influence on how they spend their money. These findings suggest that financial planning plays a crucial role in shaping wiser spending behavior among ASN.